Dynamic Load Performance of a Face Gear Drive in a Spent Fuel Reactor - Guo Mingchao; Zhang Ju; Xu Lei; Kan Chen (Jixie chuandong)
The main transmission system in a spent fuel reactor is a face gear drive, which works in concentrated nitric acid with high-temperature, and requires not to be damaged under earthquake. To design its strength reasonably, the dynamic performance of the face gear drive is studied. Its meshing principle and characteristics are briefly elaborated. The dynamic model of the face gear drive is established based on the centralized mass method.The influence of factors such as manufacturing errors and misalignments, time-varying meshing stiffness, corrosion on tooth surfaces, earthquakes on the dynamic performance are taken into consideration to deduce the differential equations of the face gear drive. Runge-Kutta method is applied to solve the differential equation, the dynamic loads under excitations of misalignment, earthquake and corrosion are obtained, and the influence law of these excitations on the dynamic load coefficient is further analyzed. The corrosion and earthquake are the key factors that cause significant increase of dynamic load coefficients, the dynamic load caused by the combined action of the considered various factors is less than twice the driving load.